Шарқ алломаларининг шахс ҳуқуқий маданиятини шакллантиришдаги ҳиссалари - Арзиева, Б.И. (SCIENCE and SOCIETY, 2022)
This country speaks about the contribution of Eastern scientists to the formation of the legal culture of the individual, the socio-pedagogical theoretical foundations of development, history and the formation of legal culture in the process of politics and education.
Keywords: orientalists; human; society; decree; law; culture; concept; right; education; ethics; school